Analisis perbezaan qiraat dalam riwayat hafs dan syu'bah terhadap ayat-ayat hukum - Kadir, Mohd. Nazir (2016)
Ilmu Qiraat is a branch of the Quranic studies which is not widely known among Muslims in Malaysia. The variety of Qiraat in Quran recitation that exist in the discipline is seen to have an impact towards the practices of Muslims in terms of arguments in Fiqh issues. However, the retrieving method and the impact of the Qiraat recitation have not been clearly nor deeply explained in books of Fiqh and Qiraat.Through the difference of Qiraat in Quran recitation that exist between the narration of Hafs and Syu‘bah, the researcher focuses and explores the function of Qiraat and its impact in Islamic Fiqh towards hukum (law) verses. This research was performed to identify the fundamentals of the differences in Qiraat between Hafs and Syu‘bah, to analyze methods of fuqaha (Fiqh scholars) towards the variety of Qiraat recitation in determining a particular hukum for a problem, to know the relevance of qurra’ (narrators) and fuqaha towards Fiqh related problems as well as identifying the impact from the influence resulting from usage of Qiraat in determining a practised hukum. This research adopted library study as a method for data collection towards primary and secondary sources to look for data in forms of historical, biographical, tafsir of a verse, and taujih Qiraat. Collected data were then analyzed based on the views of fuqaha while considering the tafsir and linguistic usage. The outcome of this research finds that eventhough Hafs and Syu‘bah acquired their recitation sanad from the same teacher, every differences in their Qiraat were received mutawatir. This research also found that two out of thirteen verses that contains differences (khilaf) in terms of Qiraat resulted in changes in determining hukum. Overall, this research indicated that ilmu Qiraat has functions and a significant role as a reference of hukum in Islam.